2019
DOI: 10.1590/0004-282x20190121
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intervention may improve migraine severity: a pilot study

Abstract: Although some studies have investigated the role of nutritional intervention on migraine, they had focused on triggers or on weight change and, to the best of our knowledge, none studied diet quality. Objective To investigate whether nutritional intervention focused on improving diet quality and healthy weight can promote improvement in clinical parameters of women with migraine. Methods Non-controlled and non-randomized intervention study conducted for 90 days. Women received an individualized diet meal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
13
0
10
Order By: Relevance
“…This study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brazil (CAAE: 12746919.5.0000.5149). This study is based on the analysis of samples previously collected by our research group between 2016 and 2019 27 …”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brazil (CAAE: 12746919.5.0000.5149). This study is based on the analysis of samples previously collected by our research group between 2016 and 2019 27 …”
Section: Methodsmentioning
confidence: 99%
“…It has also been proposed that migraine may be improved by dietary approaches with beneficial effects on the gut microbiota and gut–brain axis, including appropriate consumption of fiber, low glycemic-index diet, supplementation with vitamin D [ 68 ] and omega-3 fatty acids, low-fat vegan diet, gluten-free diet, probiotics, and weight-loss diets [ 61 ]. The latter is based on studies that have demonstrated an association between obesity and migraine and clinical improvements after weight loss [ 61 , 69 , 70 , 71 , 72 ]. For example, Verrotti et al [ 72 ] evaluated obese adolescents before and after a program involving diet, physical activity, and behavioral therapy.…”
Section: Gut–brain Axis and Probioticsmentioning
confidence: 99%
“…A proof of concept study in 2015 presented that weight loss could result in symptom improvement. 73 Based on a pilot study published in 2019, 11 enhancing the quality of diet and maintaining a healthy weight, could improve some clinical features of migraine. In this open, and nonrandomized study, women with migraine received an individualized diet plan, which was based on a professional nutritional diagnosis.…”
Section: Obesity-migraine Linkage and Weight Control In Migrainementioning
confidence: 99%
“…In this open, and nonrandomized study, women with migraine received an individualized diet plan, which was based on a professional nutritional diagnosis. This study was first to provide evidence that diet quality and maintaining a healthy weight are important, 11 not the weight loss per se. This means that for underweight patients a weight gain might be the successful strategy, while for overweight patients, a weight reduction strategy would provide beneficial effects on migraine.…”
Section: Obesity-migraine Linkage and Weight Control In Migrainementioning
confidence: 99%
See 1 more Smart Citation